Subchondral Bone Degradation After Microfracture for Osteochondral Lesions of the Talus: An MRI Analysis. Issue 3 (March 2018) - Shimozono, Yoshiharu; Coale, Max; Yasui, Youichi; O'Halloran, Amanda; Deyer, Timothy W.; Kennedy, John G.
Background: Microfracture is the most common cartilage-reparative procedure for the treatment of osteochondral lesions of the talus (OLTs). Damage to the subchondral bone (SCB) during microfracture may irreversibly change the joint-loading support of the ankle, leading to reparative fibrocartilage degradation over time. Purpose: To investigate the morphological change in the SCB after microfracture for OLT by developing a novel magnetic resonance imaging (MRI) scoring system specifically for evaluating the SCB. Furthermore, this study assesses the influence of the morphological changes of the SCB on clinical outcomes based on the new score. Study Design: Case series; Level of evidence, 4. Methods: Forty-two patients who underwent microfracture for OLT were included. An SCB Health (SCBH) scoring system was developed according to the amount of edema, subchondral cyst diameter, and qualitative and thickness change in the SCB, with a total score of 12 indicating normal SCB. MRI was obtained postoperatively from 6 months to 1 year, 1 to 2 years, 2 to 4 years, and 4 to 6 years. The Foot and Ankle Outcome Score (FAOS) was evaluated preoperatively and at 2 years and final follow-up. Results: The mean patient age was 38.4 ± 15.6 years, with a mean follow-up of 51.7 ± 22.8 months. The mean FAOS improved significantly from 57.8 ± 14.4 preoperatively to 84.3 ± 7.2 at 24 months ( P < .001) and decreased to a final mean value of 77.1 ± 12.6 ( P < .001). The mean SCBH score decreased from 8.6 ± 1.9 preoperatively to 7.1 ± 1.8 on the first follow-up MRI ( P < .001) and significantly decreased to 5.9 ± 2.3 on the fourth follow-up MRI ( P < .001). Subchondral cysts were noticeably worse at the fourth follow-up MRI than at the first and second ( P < .001, P = .006, respectively). There was a positive correlation between the final FAOS and the SCBH score on the third and fourth follow-up MRI ( r = 0.55, P < .001; r = 0.70, P < .001, respectively), but no correlation was found on the first and second follow-up. Conclusion: The SCBs following microfracture for OLT were not restored at midterm follow-up. There was a significant decrease of the overall SCBH score over time. Noticeably, subchondral cysts deteriorated over time consistently. In addition, the SCBH score at midterm follow-up was positively correlated with clinical outcomes. Lasting morphological changes in the SCB may be indicative of longer-term failure of the microfracture procedure.